Comprehensive Analysis of Differentially Expressed Profiles of mRNA N6-Methyladenosine in Colorectal Cancer - Li, Na; Guo, Qin; Zhang, Qiao; Chen, Bai-Jun; Li, Xiao-An; Zhou, Yan (Frontiers in Cell and Developmental Biology, 2022)
Aim: To comprehensively profile the landscape of the mRNA N6-methyladenosine (m6A) modification in human colorectal cancer (CRC). Methods: Methylated RNA immunoprecipitation sequencing (MeRIP-seq) was explored to compare the difference in mRNA N6-methyladenosine (m6A) methylation between CRC tissues and adjacent normal control (NC) tissue. RNA-sequencing (RNA-seq) was performed to transcribe differentially expressed mRNAs. Conjoint analysis of MeRIP-seq and RNA-seq data was conducted to predict RNA-binding proteins (RBPs). Results: MeRIP-seq identified 1110 differentially m6A methylated sites (DMMSs) and 980 differentially m6A methylated genes (DMMGs) in CRC, with 50.13% of all modified genes showing unique m6A-modified peaks in CRC. Conjoint analysis of MeRIP-seq and RNA-seq identified 400 differentially m6A methylated and differentially expressed genes (DEGs), and indicated a positive correlation between methylation and expression. Pathway analysis detected that DMMGs and DEGs were mainly enriched in Spindle and Nuclear division, calcium signaling pathway, cell cycle and protein processing endoplasmic reticulum pathways etc. After analyzing these DMMGs and DEGs through the GEPIA database, we found that low expression of B3GNT6 (HGNC:24141) in colon cancer (COAD), DKC1 (HGNC:2890) and SRPK1 (HGNC:11305) in rectal cancer (READ) together with high expression of RIMKLB (HGNC:29228) in COAD were associated with worse prognosis. 17RBPs were identified based on the DMMGs and DEGs, among which FMR1 (HGNC:3775), IGF2BP2 (HGNC:28867) and SRSF1 (HGNC:10780) were closely related to the transport between the nucleus and cytoplasm, and might be involved in the development of CRC. Conclusions: This study comprehensively profiles m6A modification of mRNAs in CRC, which reveal possible mechanisms of m6A-mediated gene expression regulation.